Impacts of vitamin A deficiency on biological rhythms: Insights from the literature - Guo, Xiangrong; Wang, Hui; Xu, Jian; Hua, Hui (Frontiers in Nutrition, 2022)
Vitamin A is essential for brain function, in addition to its important roles in vision, immunity, and reproduction. Previous studies have shown that retinoic acid (RA), the bioactive form of vitamin A, is involved in the regulation of various intracellular responses related to biological rhythms. RA is reported to affect the circadian rhythm by binding to RA receptors, such as receptors in the circadian feedback loops in the mammalian suprachiasmatic nucleus. However, evidence of the impacts of vitamin A deficiency (VAD) on biological rhythms is limited, and most of the related studies were conducted on animals. In this review, we described the physiological functions of biological rhythms and physiological pathways/molecular mechanisms regulating the biological rhythms. We then discussed the current understanding of the associations of VAD with biological rhythm disorders/diseases (sleep disorders, impairments in learning/memory, emotional disorders, and other immune or metabolism diseases) and summarized the currently proposed mechanisms (mainly by retinoid nuclear receptors and related proteins) for the associations. This review may help recognize the role of VAD in biological rhythm disorders and stimulate clinical or epidemiological studies to confirm the findings of related animal studies.